1988
DOI: 10.1152/jappl.1988.64.3.1107
|View full text |Cite
|
Sign up to set email alerts
|

Increasing duration of smoke exposure induces more severe lung injury in sheep

Abstract: Eighteen sheep previously prepared for chronic study were divided into three groups of six animals each. These were given graded inhalation injury utilizing smoke obtained from burning cotton-toweling material. Smoke was insufflated into animals with a modified bee smoker at temperatures less than 40 degrees C. Group H, which received 64 breaths of smoke, showed the most pronounced changes in pulmonary function. The changes consisted mainly of a profound increase in lung lymph flow following a reduced P/F rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(60 citation statements)
references
References 0 publications
1
59
0
Order By: Relevance
“…Beckman and colleagues [55] reported that the prevention of decomposition of NOx by scavenging superoxide anion using superoxide dismutase (SOD) reduced the tissue 3-nitrotyrosine content. We have previously measured the chemical content of the smoke from burning cotton [56]. The majority of the offending materials were aldehydes and acrolein.…”
Section: Discussionmentioning
confidence: 99%
“…Beckman and colleagues [55] reported that the prevention of decomposition of NOx by scavenging superoxide anion using superoxide dismutase (SOD) reduced the tissue 3-nitrotyrosine content. We have previously measured the chemical content of the smoke from burning cotton [56]. The majority of the offending materials were aldehydes and acrolein.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep were surgically prepared for chronic study, as described previously (19)(20)(21). Briefly, a Swan-Ganz thermal dilution catheter (model 93A-1317-F, Edwards Critical Care Division; Irvine, CA) was inserted through the right external jugular vein for the measurement of cardiac output and the core body temperature and measure the central venous pressure to evaluate fluid resuscitation.…”
Section: Surgical Preparation and Injurymentioning
confidence: 99%
“…The smoke and burn injury protocol was described previously (19)(20)(21). Briefly, under induction of anesthesia with 10 mg/kg ketamine (Ketalar; Parke-Davis; Morris Plains, NJ), a tracheotomy was performed, and a cuffed tracheostomy tube (10-mm diameter, Sheiley; Irvine, CA) was inserted.…”
Section: Surgical Preparation and Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in numerous human and experimental animal models, the response may be attributed to smoke combustion products, heat, and hypoxia environment. Detailed examinations have indicated the characterized airway damage induced by FS could be reproduced by the airway nebulization of acrolein, one of numerous aldehydes among smoke combustion products (18,25). These are some of the chemicals that have been recognized to have obvious sensory neurotoxicity in the lungs (27,48).…”
mentioning
confidence: 99%